The face, the future, and dental practice: how research in craniofacial biology will influence patient care. (20th March 2014) - Townsend, GC; Brook, AH
Abstract: It has been a privilege to assemble a group of Australian and international researchers to produce a special issue of the Australian Dental Journal that reflects the cutting edge of research in different aspects of craniofacial biology, and also considers how these advances will influence future education and practice within dentistry. The aim of this special issue is to provide a collection of concept papers and critical reviews on key topics that cover both fundamental and applied research in craniofacial biology and to consider the clinical implications. To do this, four questions have been addressed that lead to the four sections of this issue. These are: How have we come to the present exciting position in craniofacial biology with breakthroughs over the past 50 years? What are current fundamental research topics that are helping us to understand more about craniofacial and general development, possibly leading to future clinical developments? What are the current applied research topics that will influence future clinical practice? Looking forward, what new developments in craniofacial biology may come about that will change the face of dental education and practice? The refereed papers in this special issue are grouped into the four sections that seek to respond to these demanding questions.